2017
DOI: 10.3390/f8030074
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sap Flow Density and  Environmental Factors in the Yangtze River Delta  Region of China

Abstract: Abstract:Canopy transpiration is an important component of evapotranspiration, integrating physical and biological processes within the water and energy cycles of forests. Quercus acutissima and Cunninghamia lanceolata are two important, fast-growing and commercial tree species that have been extensively used for vegetation restoration, water conservation and building artificial forests in the Yangtze River Delta region of China. The primary objective of this study was to characterize sap flow densities of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
6
18
0
Order By: Relevance
“…However, in contrast to our study, they found that higher levels of nocturnal sap flow occurred during the dry period than the wet period. Liu et al [72] reported similar seasonality of nocturnal sap flow as found in our study. According to these authors, the reason for this seasonality is because the nighttime period during spring and autumn is longer than in summer, meaning there is more time for nocturnal sap flow to accumulate.…”
Section: Parametersupporting
confidence: 91%
“…However, in contrast to our study, they found that higher levels of nocturnal sap flow occurred during the dry period than the wet period. Liu et al [72] reported similar seasonality of nocturnal sap flow as found in our study. According to these authors, the reason for this seasonality is because the nighttime period during spring and autumn is longer than in summer, meaning there is more time for nocturnal sap flow to accumulate.…”
Section: Parametersupporting
confidence: 91%
“…High soil water content is beneficial for root water uptake, increasing sap flow. A number of research papers reported that sap flow was positively correlated with air temperature [6,56,57], and this was consistent with our results. Generally, high air temperature increased transpiration and promoted sap flow.…”
Section: Environmental Control On Sap Flow Density and Tree Water Defsupporting
confidence: 93%
“…Water use by a tree is regulated by environmental factors [15,18,51]. Most studies indicate that sap flow in a tree is strongly affected by VPD [35,52,53]. The rate of transpiration of redcedar increased with increasing VPD and the availability of soil water [15,18].…”
Section: S D Day and Environmental Variablesmentioning
confidence: 99%